Answer:
I'm doing the same thing and, I don't understand it either.
Step-by-step explanation:
Answer:
1. Pyramid= ll+l^2 2. Rectangular prism= 2 lw+2lh+2wh 3. Cylinder= 2pi pi rh+2pi pi r^2 4.Triangular Prism= 2 B + Ph 5. Cone= Pi rl+ pi r^2
Step-by-step explanation:
Pretty sure this is your answer. Hope it helps!
Y - 11 = 3(x + 4)....distribute thru the parenthesis
y - 11 = 3x + 12....add 11 to both sides
y = 3x + 12 + 11...simplify
y = 3x + 23 <==
Answer:
36years
Step-by-step explanation:
Let charity present age be x
Charity daughter present age be y
Charity husband present age be z
If the sum of their ages ten years to come is 117, then;
10+x+10+y+10+z = 117
30+x+y+z = 117
x+y+z = 87 ... 1
If charity is four times as old as her daughter, then;
x = 4y
y = x/4 ... 2
If she is also six years younger than her husband, then;
x = z- 6
z = x+6 .. 3
Substitute 2 and 3 into 1;
x + x/4 + (x+6) = 87
Multiply through by 4
4x + x + 4(x+6) = 4(87)
5x+4x+24 = 348
9x = 348 - 24
9x = 324
x = 324/9
x = 36
hence Charity is 36years old today
Answer:
-55
Step-by-step explanation:
the sqeuence seems to be subtracting by 2 everytime.
so it will be -1,-3,-5,-7,-9,-11,-13,-15,-17,-19,-21,-23,-25,-27,-29..
the answer will be 27*-2(-54) -1(because we start at -1 , not 0)